Горячий снег - Бондарев Юрий Васильевич (Библиотека мировой литературы для детей, 1986)
Экземпляры: (20220701) / Инвентарный номер: 11423(А) / Сис.шифр: 84(2=Рус)7-44 / Авт.знак: Б 81 / ББК: 84(2=Рус)7-44